Crucial findings from the 4W model of drowning for practical and teaching Applications - Avramidis, S.; McKenna, J.; Long, J.; Butterly, R.; Llewellyn, J. D. (Biomechanics and Medicine in Swimming XI, 2010)
This study aimed to suggest practical and teaching applications of the 4W model of drowning. A major literature review of quantitative research was undertaken to identify potential risk factors of drowning and qualitative content analysis was used to analyze publicly available drowning incident videos (n = 41, M = 345.0, SD = 2.8), and 34 individuals involved in drowning incidents were interviewed (30 males age 16-65 years, M = 28.4, SD = 11.3; 4 female age 19-65 years, M = 37.5, SD = 19.5). Results confirmed that test criteria such as a 100 m run-50 m swim-100 m run for open water and a 50 m run-20 m swim-50 m run for pool/water parks could be more useful for assessing speed combined with an `early approach` to the victim than any currently in operation. The `early approach` criterion would be established to test the ability of the lifeguard to be able to remain alert, to have good vision, to recognize the casualty`s instinctive drowning response, to initiate a rescue ignoring the bystander`s lack of response and to reassure the drowning victim. Drownings and their rescue interventions should be perceived as 3-dimensional problems.